A Study of Hand Flap Viability when Using a Wide Awake Local Anesthesia No Tourniquet (WALANT) Technique - Prénaud, Clément; Merlini, Lorenzo; Hurst, Simon A.; Gregory, Thomas; Dacheux, Charles (Journal of Hand and Microsurgery, 2022)
Objectives Flap surgery using a wide awake local anesthesia no tourniquet (WALANT) technique has historically been avoided because of technical challenges and concerns regarding the vasoconstriction caused by the necessary injection of epinephrine alongside the local anesthetic. The objective of our work was to evaluate the viability of the hand flaps performed using a WALANT technique compared with those performed under regional with a tourniquet.Materials and Methods Seventy-four patients were enrolled in a prospective comparative single-center study and subsequently divided into two groups: 36 patients in the locoregional anesthesia group and 38 patients in the WALANT group. Flap viability was evaluated on day 2 and day 10 using predetermined criteria.Results We did not find any significant difference in outcomes assessed for flap viability between the two groups postoperatively.Conclusion There was no evidence to suggest that vascularization of the flaps was compromised by the injection of epinephrine. The WALANT technique may, therefore, potentially be able to be safely deployed within this population.
Keywords: anesthesia; flaps; viability